The Impact of Digital Transformation on Firm Value: A Study of Publicly Listed Companies on the Indonesia Stock Exchange - Frimayasa, Agtovia; Mutaqqin, Hakim; Magalhaes, Cancio Andika Irawan; Ratnawati, Tri (Jurnal Multidisiplin Sahombu, 2025)
This study investigates the impact of digital transformation on firm value among publicly listed companies on the Indonesia Stock Exchange (IDX), with a comparative focus on the banking and consumer goods sectors. Using secondary data from 2018 to 2022, the study employs multiple linear regression for the banking sector and panel data regression with the Fixed Effect Model for the consumer goods sector. The results reveal that digital transformation has a significant positive effect on financial performance (ROA) in the banking sector, while its impact on market value (PBV) in the consumer goods sector is not statistically significant. Firm size acts as a moderating variable that enhances the relationship between digital transformation and firm value, particularly in the banking sector. These findings underscore the importance of digital maturity, organizational readiness, and strategic alignment in leveraging technology for value creation. The study contributes to the literature by highlighting sectoral differences in the effectiveness of digital transformation.